Concept of Aahara According to Prakrti -A Review - Kumari, Anita; Sharma, Manish Kumar; Khan, Iqbal; Sharma , Ashok Kumar; Sharma, K L; Meena , Rekhraj; Nigam, Ayushi (International Research Journal of Ayurveda & Yoga, 2022)
Ayurveda the “Science of life” is a system of medicine that utilizes various therapies including diet , herbal preparations and yoga to restore harmony balance with in the body. It focuses more on the healthy living and well being. One of the main goals of Ayurveda is to maintain health of a healthy individual and to attain the health in the diseased. Diet is mentioned in 3 sub – pillar (sub tripods of life), since it is responsible is for growth & development of the human body. One of the important concepts in Ayurveda is “Prakriti” the innate nature of an individual & is determined at the time of conception itself & remains throughout the life. Knowing of Prakriti helps in maintaining the health and preventing the disease. Ayurveda prescribes various foods and lifestyles According to one’s Prakriti and suggests that one should follow these guidelines to prevent various disorders and to promote health. In this era of lifestyle disorders in order to improve the quality of life & to bring down the cost of health care one should know about his Prakriti & the diet suitable for his body constitution .Here by this paper is intended to explain the concepts of diet in Ayurveda in a backlight of Prakriti.